2021
DOI: 10.31290/jpk.v10i1.2256
|View full text |Cite
|
Sign up to set email alerts
|

Pengaruh Terapi Dzikir Terhadap Skala Nyeri Pasien Post Operasi

Abstract: Permasalahan pada pasien post operasi adalah rasa nyeri yang dirasakan akibat luka operasi. Setelah efek anestesi hilang maka pasien akan merasakan nyeri pada area dilakukan tindakan operasi. Hal ini akan mengakibatkan pasien merasa tidak nyaman, tidak tenang, gelisah dan berbagai gangguan perasaan atau mood lainnya. Secara fisiologis, dzikir akan menghasilkan beberapa efek medis dan psikologis yaitu akan membuat  seimbang  kadar  serotonin  dan  norepineprin  di  dalam  tubuh.  Hal tersebut  merupakan  morfin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
2
0
3

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 0 publications
0
2
0
3
Order By: Relevance
“…Dzikir is a collection of sentences spoken in order to remember Allah SWT, to keep going and stay away from his prohibitions (Himawan et al, 2019). Dzikir therapy can make patients feel more relaxed, thereby suppressing the work of the sympathetic system and activating the parasympathetic system (Jannah & Riyadi, 2021). Therefore, researchers are interested in applying Dzikir Relaxation Therapy for Acute Pain in Abdominal Pain Patients at the emergency room of PKU Aisyiyah Boyolali Hospital.…”
Section: Introductionmentioning
confidence: 99%
“…Dzikir is a collection of sentences spoken in order to remember Allah SWT, to keep going and stay away from his prohibitions (Himawan et al, 2019). Dzikir therapy can make patients feel more relaxed, thereby suppressing the work of the sympathetic system and activating the parasympathetic system (Jannah & Riyadi, 2021). Therefore, researchers are interested in applying Dzikir Relaxation Therapy for Acute Pain in Abdominal Pain Patients at the emergency room of PKU Aisyiyah Boyolali Hospital.…”
Section: Introductionmentioning
confidence: 99%
“…Previous research showed that the average pain scale before dhikr therapy was 4.95, and the average pain scale after dhikr therapy was 3.90. So, dhikr therapy has an effect on the postoperative pain scale (Jannah et al, 2021). This movement is carried out gradually to reduce the intensity of pain and create a calm appearance so that shortening the duration of pain episodes often lasts only a few seconds or minutes.…”
Section: Introductionmentioning
confidence: 99%
“…Pada pasien post operasi biasanya sering mengeluh nyeri karena sayaatan pada luka operasi. Setelah efek anastesi menghilang, pasien akan terasa nyeri di daerah luka sayatan yang akan menyebabkan ketidaknayamanan, maupun gelisah yang dirasakan oleh pasien (Jannah et al, 2021). Selain itu dengan adanya nyeri akan berpengaruh dengan aktivitas, nafsu makan dan hubungan emosional dari pasien (Hermanto et al, 2020).…”
Section: Introductionunclassified
“…Dzikir adalah sekumpulan kalimat yang diucapkan agar mengingat Allah SWT, agar tetap dijalannya dan menjauhi larangannya (Himawan et al, 2019). Terapi dzikir dapat membuat pasien merasakan lebih rileks, sehingga menekan kerja sistem simpatik dan mengaktifkan sistem parasimpatis (Jannah et al, 2021). (Jannah, 2021).…”
Section: Introductionunclassified
See 1 more Smart Citation